Biomechanical evaluation of prophylactic reinforcement of the linea alba with a novel method of positioning and fixation of polypropylene mesh, in an animal model - Thiago de Almeida Furtado; Álvaro Cota Carvalho; Marcelo Lopes Furtado; Luiz Ronaldo Alberti; Diego Paim de Carvalho Garcia (Acta Cirúrgica Brasileira)
ABSTRACT Purpose: To evaluate the effectiveness of a new format of prophylactic mesh, with a new method of placement. Methods: Rabbits were randomly distributed into four groups: control rabbits without laparotomy group; sutured rabbits (SR); light-weight mesh rabbits (LWMR); and heavy-weight mesh rabbits (HWMR). The meshes were cut to a size of 10 cm in length by 1 cm in width. A longitudinal, median abdominal incision, 11 cm in length, was performed, followed by an incision over the linea alba, encompassing the entire thickness of the abdominal wall. On the 91st postoperative day, the animals were killed for linea alba scar evaluation. Results: There was a significant difference among the evaluated groups concerning elongation, maximum load, and elasticity modulus. HWMR and LWMR were statistically different from controls regarding elongation. As for the elasticity modulus, SR presented a higher mean when compared to the others. Microscopic visual analysis showed greater fibrotic scarring with a larger amount of implanted material in HWMR. Conclusion: The reinforcement of scars with polypropylene mesh does not increase tensile strength when compared to the use of sutures. Mesh implantation results in scar remodeling with greater fibrosis, leading to increased elongation. However, midline reinforcement using only sutures has greater elasticity than the groups reinforced with mesh.